THE CORRELATION BETWEEN MOTIVATION AND SPEAKING ABILITY OF THE SECOND YEAR STUDENTS OF SMK MUHAMMADIYAH 2 PEKANBARU - Lestari, Puji; Mahdum, Mahdum; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Absratct: This research aimed to determine the correlation between the motivation and speaking ability of the second year students of SMK Muhammadiyah 2 Pekanbaru. The sample of this research was all class of the second year students consisted of 37 students. The sample was chosen by using Proportional Sampling Techniques. To collect the data in this research were questionnaire and speaking test. The motivation data was gained by using Attitude/Motivation Test Battery (AMBT) questionnaire by Gardner and the speaking ability data was gained by monologue test. The results of the study show that there was a correlation between two variables. The value of correlation coefficient was 0.643. It was on scale 0.60 ? 0.799 it meant that the correlation between students? motivation and speaking ability of the second year students of SMK Muhammadiyah 2 Pekanbaru categorized as high correlation. It is considered that null hypothesis (Ho) is rejected, while the alternative hypothesis (Ha) is accepted. So, it can be concluded that there was a significant correlation between the motivation and speaking ability of the second year students of SMK Muhammadiyah 2 Pekanbaru. In other words, the students? motivation affects their speaking ability.Key Words: Correlation, Motivation, Speaking Ability